Miniaturized label-free smartphone assisted electrochemical sensing approach for personalized COVID-19 diagnosis - Chandra P. (My University, 2025)
The COVID-19, coronavirus disease is an infectious disease caused by a novel virus called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). By March 2020 the novel coronavirus known to cause a pandemic has infected nearly about 119 thousand people and killed more than 4,300 around 114 countries. Apart from the current controversial opinions about the origin, spreading, and sociological impact, it is much more imperative to put a halt to this current situation. Understanding, testing, and early to rapid diagnosis may be now the only key that can contain COVID-19 by “flattening the curve”. Biosensing is the platform that allows rapid, highly sensitive, and selective detection of analytes which in turn can serve the purpose for fast and precise detection of COVID-19. In this article, based on recently reported miniaturized sensing strategies, we hereby propose a promising personalized smartphone assisted electrochemical sensing platform for diagnosis of COVID-19. © 2020 The Author